The influence of tax labeling and tax earmarking on the willingness to contribute: A conjoint analysis - Jochen Hundsdoerfer; Christian Sielaff; Kay Blaufus; Dirk Kiesewetter; Joachim Weimann (Arbeitskreis Quantitative Steuerlehre (arqus), 2011)
We apply conjoint analysis to study the influence of tax labeling and tax earmarking on German taxpayers' willingness to contribute. From a survey based sample we show that labeling and earmarking effects can substantially increase participants' willingness to contribute, which results in a considerable deviation from a pure consumption maximizing behavior. Furthermore, we give an explanation for this effect regarding socio-demographic attributes of German taxpayers. These results explain the variety in tax labels and provide implications for tax policy regarding further reforms of the tax and contribution system: Labeling and earmarking of contributions are important instruments in selling policies and increasing tax revenue.
Keywords: D03; H20; H51; H52; K34; 330; Behavioral Taxation; Tax Labeling; Tax Earmarking; Willingness to Contribute; Conjoint Analysis; Perceived Tax Burden; Steuermoral; Steuerpolitik; Steuerbelastung; Wahrnehmung; Conjoint-Analyse; Deutschland